2021
DOI: 10.1055/s-0041-1735441
|View full text |Cite
|
Sign up to set email alerts
|

Displaced Radial Neck Fractures in the Paediatric Age Group Fixed with the Modified Metaizeau Technique: Experience of a Tertiary Care Hospital in Northern India

Abstract: Background Radial neck fractures in the pediatric population represent up to one percent of all pediatric fractures. Judet type III and IV radial neck fractures present difficulties in closed and open reduction. The Metaizeau technique has been used as a tool to reduce these. We present a case series of 17 patients with Judet III and IV type of radial neck fractures treated with a modified Metaizeau technique. Materials and Methods Seventeen patients, eight male and nine female with Judet type III an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Regarding complications, no complications were reported in our study. This comes in agreement with Kansay et al (30) who reported no complications. Also, Ursei et al (14) demonstrated that there was no instance of neurovascular deficit, heterotopic bone formation and radioulnar synostosis or infectious complications during their study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding complications, no complications were reported in our study. This comes in agreement with Kansay et al (30) who reported no complications. Also, Ursei et al (14) demonstrated that there was no instance of neurovascular deficit, heterotopic bone formation and radioulnar synostosis or infectious complications during their study.…”
Section: Discussionsupporting
confidence: 93%
“…Outcomes showed that 82% reported excellent and the remaining had good outcomes. Kansay et al (30) study had 76% excellent outcomes amongst seventeen patients. They reported no complications.…”
Section: Discussionmentioning
confidence: 91%
“…In a study by Prasarn et al, they stated that the posterior approach carries a risk of nerve damage because the plate must be placed under the radial nerve [24]. In many studies, radial nerve palsy was found to be more common in patients who underwent the posterior approach than in the patients who underwent the anterolateral approach [9,25]. In our study, although the rate of radial nerve palsy was higher in patients operated on with the posterior approach than in the patients who underwent the anterolateral approach, it was not significant.…”
Section: Type Of Incision P-value Posterior (N=29)mentioning
confidence: 99%
“…The patients' Mayo elbow performance score was used, consisting of four components: Pain, Movement, Stability, and Function; the maximum possible score is 100. The Mayo elbow performance score is a reliable and valid tool for assessing elbow function [9].…”
Section: Introductionmentioning
confidence: 99%